Diverticulitis Management, a Snapshot Collaborative Audit Study (DAMASCUS): Protocol for an international, multicentre, prospective observational study. (15th May 2021) - ,
Abstract: Aim: Diverticular disease is an increasingly common problem in Western society with a variety of treatment options for those presenting with acute diverticulitis, dependent on clinical presentation. Additionally, there is significant international variability in the index management, and few published data on real‐world clinical practice. The aim of DAMASCUS is to identify areas of practice variability and their potential association with differences in short‐ and medium‐term clinical outcomes. Methods and analysis: DAMASCUS is an international, collaborative, prospective observational study, recruiting patients from over 200 sites across six continents. The study opened in October 2020, with a rolling start. Identification of new sites ceased in February 2021 and data collection will cease in August 2021. All adult patients diagnosed with acute diverticulitis (radiologically or intra‐operatively) at each participating centre will be included. The primary objective of DAMASCUS is to assess for national and international variability in the presentation and index management of acute diverticulitis (medical, interventional radiology and surgical). Secondary objectives include assessing 30‐day and 6‐month clinical outcome data (readmission, re‐intervention, morbidity and mortality) and variations in surgical procedures for those undergoing surgery. All data will be recorded and managed using a secure REDCap electronic data capture tool and analysed using Stata (SE) version 16.1. The results will be reported in accordance with the STROBE statement. Conclusion: By analysing variations in the management of acute diverticulitis and the subsequent outcomes, DAMASCUS will be an important step towards identifying optimal care for patients with diverticulitis.